Effectiveness Of Buerger Allen Exercise Among Pregnant Women With Restless Leg Syndrome In A Selected Hospital Banke, Nepal - Srijana Sapkota (DIROSAT: Journal of Education, Social Sciences & Humanities, 2023)
Restless Leg Syndrome is a neuromuscular sensorimotor disorder characterized by uncontrolled urge to move the affected legs which is accompanied by distressing parathesia of the leg, described as” creeping, tugging and pulling feeling.”. The aim of the study was to evaluate the effectiveness of Buerger Allen exercise among pregnant women with Restless Leg Syndrome. Methods:  A Quasi experimental design was carried out to evaluate the effectiveness of buerger allen exercise with a total of 60 pregnant women (n = 30 in the control group who did not receive exercise intervention and n = 30 in the experimental group who received Buerger Allen Exercise). The data was collected within the period of 27th November 2017 to 27th December 2017 using non-probability purposive sampling technique. Data was collected through modified International Restless Legs Syndrome Scale (IRLSS). Collected data were entered in Statistical Package 21 version and analyzed by using mean and repeated measures analysis of variance. When analyzing symptoms of Restless leg syndrome over time a significant difference was found between two groups where the mean restless leg syndrome severity score of the experimental group who had performed buerger allen exercise as an adjunct to no intervention being noted to be lower than that of the control group. A statistically significant reduction of symptoms was observed in the experimental group (P < .005).  Conclusion: The study concluded that the Buerger Allen exercise helps in reduction of symptoms of Restless leg syndrome among pregnant women.